2017
DOI: 10.1161/circep.116.004738
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Structure and Function Are Associated With Incident Atrial Fibrillation

Abstract: Background Right ventricular (RV) morphology has been associated with drivers of atrial fibrillation (AF) risk including left ventricular (LV) and pulmonary pathology, systemic inflammation and neurohormonal activation. The aim of this study was to investigate the association between RV morphology and risk of incident AF. Methods and Results We interpreted cardiac magnetic resonance (CMR) imaging in 4,204 participants free of clinical cardiovascular disease in the Multi-Ethnic Study of Atherosclerosis (MESA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Additionally, we adjusted for LA, left ventricular (LV), and RV variables as obtained from and described in previous studies in MESA [5,7,21]. In brief, the LA variables most closely associated with incident AF were: elevated LA maximum volume index (adjusted HR 1.38, p = 0.04), passive LA EF (adjusted HR 0.55, p < 0.001), and peak LA strain (adjusted HR = 0.68, p = 0.031).…”
Section: Covariatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we adjusted for LA, left ventricular (LV), and RV variables as obtained from and described in previous studies in MESA [5,7,21]. In brief, the LA variables most closely associated with incident AF were: elevated LA maximum volume index (adjusted HR 1.38, p = 0.04), passive LA EF (adjusted HR 0.55, p < 0.001), and peak LA strain (adjusted HR = 0.68, p = 0.031).…”
Section: Covariatesmentioning
confidence: 99%
“…We additionally created models adjusting for demographics, traditional risk factors, and RV variables previously identified as being associated with incident AF [7] (Additional file 2). RAVI max was significant in fully adjusted models including RV EF and mass (HR per SD:…”
Section: Association Of Ra Parameters and Incident Afmentioning
confidence: 99%
See 1 more Smart Citation
“…AF, coincidentally with diastolic dysfunction or not, may cause structural right heart change through electrical remodeling. 25 TR with postcapillary pulmonary hypertension due to diastolic dysfunction and elevated LV end-diastolic pressure was the dominant form in the present study. Thus, in the present study, a substantial proportion of patients had isolated secondary (functional) TR.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, is highly expressed in human stem cell-derived cardio myoblasts and it has been reported as a one of the major atrial fibrillation (AF) susceptibility-conferring genes and an important regulatory factor which modifies circadian function ( 48 51 ). Indeed, several studies have reported ventricular enlargement associated with AF and other related cardiovascular phenotypes ( 52 54 ). This is in agreement with some other studies consistently suggesting that ventricular dysfunction and AF reduce cerebral blood flow exerting negative influences on cognitive function along in the aging process ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%